Math Formula PDF Download For 6 Class, 7 Class, 8 Class, 9 Class, 10 Class, 11 Class, 12 Class All Formulas PDF: Hey friends, today we have essential math formulas for every candidate, because Basic Math Formula is also available in Hindi And English, and below we have also made Basic Math Formula PDF Download available, which Math Formula PDF can access 1500 through the button given below.

And More Math Formula PDF can download important Math Formula PDF, first read about these notes issued below correctly. Let us tell you that, Math Formula is essential for SSC Exams, Bank, Railway, And Other One Day Examination,  All Exams Math Formula Notes every student must remember, questions come from Math Subjects in any exam.

## Math Formulas For 6 Class, 7 Class, 8 Class, 9 Class, 10 Class, 11 Class, 12 Class Download

We will tell you in detail below what things are available in any way in the open PDF and its quality so that you do not have any doubts about Maths Subjects.

1. Number Sets
2. Algebra
3. Geometry
4. Trigonometry
5. Matrices And Determinants
6. Vectors
7. Analytic Geometry
8. Differential Calculus
9. Integral Calculus
10. Differential Equations
11. Series
12. Probability

## Math Formula PDF Download Latest For 6 Class, 7 Class, 8 Class, 9 Class, 10 Class, 11 Class, 12 Class

First of all, check below the size of available  Math Formula Notes, and in which language, who has prepared, and check it before downloading.

Natural Numbers –  a n  – b n  = (a – b)(a n-1  + a n-2  +…+ b n-2 a + b n-1 )

Even -  (n = 2k), an + bn = (a + b)(an-1 – an-2b +…+ bn-2a – bn-1)

Odd Numbers (Odd) -  (n = 2k + 1), a n  + b n  = (a + b)(a n-1  – a n-2 b +…- b n-2 a + b n-1 ) (a + b + c + …)2 = a2 + b2 + c2 + … + 2(ab + ac + bc + ….

### Low Of Formula Exponents

(am)(an) = am+n

(ab)m = ambm

(am)n = amn

a2 – b2 = (a – b)(a + b)

(a+b)2 = a2 + 2ab + b2

a2 + b2 = (a – b)2 + 2ab

(a – b)2 = a2 – 2ab + b2

(a + b + c)2 = a2 + b2 + c2 + 2ab + 2ac + 2bc

(a – b – c)2 = a2 + b2 + c2 – 2ab – 2ac + 2bc(a + b) 3  = a 3  + 3a 2 b + 3ab 2  + b 3  ; (a + b) 3  = a 3  + b 3  + 3ab(a + b)

(a – b) 3  = a 3  – 3a 2 b + 3ab 2  – b 3

a3 – b3 = (a – b)(a2 + ab + b2)

a3 + b3 = (a + b)(a2 – ab + b2)

(a + b) 3  = a 3  + 3a 2 b + 3ab 2  + b 3

(a – b) 3  = a 3  – 3a 2 b + 3ab 2  – b 3

(a + b)4 = a4 + 4a3b + 6a2b2 + 4ab3 + b4)

(a – b)4 = a4 – 4a3b + 6a2b2 – 4ab3 + b4)

a4 – b4 = (a – b)(a + b)(a2 + b2)

a 5  – b 5  = (a – b) (a 4  + a 3 b + a 2 b 2  + ab 3  + b 4 )

Some important  Math Formula Notes are also available below, which can be downloaded easily.

### Trigonometry Math Formulas

Ѕιη0 ° = 0

ѕιη30 ° = 1/2

ѕιη45 ° = 1 / √2

ѕιη60 ° = √3 / 2

ѕιη90 ° = 1

¢ σѕ ιѕ σρρσѕιтє σƒ ѕιη

ταη0 ° = 0

тαη30 ° = 1 / √3

тαη45 ° = 1

тαη60 ° = √3

тαη90 ° = ∞

¢ στ ιѕ σρρσѕιтє σƒ тαη

ѕє ¢ 0 ° = 1

ѕє ¢ 30 ° = 2 / √3

ѕє ¢ 45 ° = √ 2

ѕє ¢ 60 ° = 2

ѕє ¢ 90 ° = ∞

є σѕє ¢ ιѕ σρρσѕιтє σƒ ѕє ¢

2ѕιηα ¢ σѕв = ѕιη (α + в) + ѕιη (α-в)

2 ¢ σѕαѕιηв = ѕιη (α + в) -ѕιη (α-в)

2 ¢ σѕα ¢ σѕв = ¢ σѕ (α + в) + ¢ σѕ (α-в)

2ѕιηαѕιηв = ¢ σѕ (α-в) - ¢ σѕ (α + в)

Ѕιη (α + в) = ѕιηα ¢ σѕв + ¢ σѕα ѕιηв.

¢ σѕ (α + в) = ¢ σѕα ¢ σѕв - ѕιηα ѕιηв.

Ѕιη (α-в) = ѕιηα ¢ σѕв- ¢ σѕαѕιηв.

Ѕ σѕ (α-в) = ¢ σѕα ¢ σѕв + ѕιηαѕιηв.

Тαη (α + в) = (тαηα + тαηв) / (1 − тαηαтαηв)

тαη (α − в) = (тαηα - тαηв) / (1+ тαηαтαηв)

¢ στ (α + в) = (¢ στα ¢ στв −1) / (¢ στα + ¢ στв)

¢ στ (α − в) = (¢ στα ¢ σтв + 1) / (¢ σтв− ¢ στα)

Ѕιη (α + в) = ѕιηα ¢ σѕв + ¢ σѕα ѕιηв.

¢ σѕ (α + в) = ¢ σѕα ¢ σѕв + ѕιηα ѕιηв.

Ѕιη (α-в) = ѕιηα ¢ σѕв- ¢ σѕαѕιηв.

Ѕ σѕ (α-в) = ¢ σѕα ¢ σѕв + ѕιηαѕιηв.

Тαη (α + в) = (тαηα + тαηв) / (1 − тαηαтαηв)

тαη (α − в) = (тαηα - тαηв) / (1+ тαηαтαηв)

¢ στ (α + в) = (¢ στα ¢ σтв −1) / (¢ στα + ¢ στв)

¢ στ (α − в) = (¢ στα ¢ σтв + 1) / (¢ σтв− ¢ στα)
α / ѕιηα = в / ѕιηв = ¢ / ѕιη ¢ = 2я

α = в ¢ σѕ ¢ + ¢ ¢ σѕв

в = α ¢ σѕ ¢ + ¢ ¢ σѕα

¢ = α ¢ σѕβ + в ¢ σѕα

¢ σѕα = (в² + ¢ ²− α²) / 2в ¢

¢ σѕв = (¢ ² + α²− в²) / 2 ¢ α

¢ σѕ ¢ = (α² + в²− ¢ ²) / 2 ¢ α

Δ = αв ¢ / 4я

ѕιηΘ = 0 тнєη, Θ = ηΠ

ѕιηΘ = 1 тнєη, Θ = (4th + 1) Π / 2

ѕιηΘ = −1 тнєη, Θ = (4η− 1) Π / 2

ѕιηΘ = ѕιηα тнєη, Θ = ηΠ (−1) ^ ηα

## Algebra Formulas

$$a^{2}-b^{2}=(a+b)(a-b)$$

$$(a+b)^{2}=a^{2}+2 a b+b^{2}$$

$$a^{2}+b^{2}=(a-b)^{2}+2 a b$$

$$(a-b)^{2}=a^{2}-2 a b+b^{2}$$

$$(a+b+c)^{2}=a^{2}+b^{2}+c^{2}+2 a b+2 a c+2 b c$$

$$(a-b-c)^{2}=a^{2}+b^{2}+c^{2}-2 a b-2 a c+2 b c$$

$$(a-b)^{3}=a^{3}-3 a^{2} b+3 a b^{2}-b^{3}$$

$$a^{3}-b^{3}=(a-b)\left(a^{2}+a b+b^{2}\right)$$

$$a^{3}+b^{3}=(a+b)\left(a^{2}-a b+b^{2}\right)$$

$$(a+b)^{3}=a^{3}+3 a^{2} b+3 a b^{2}+b^{3} ;(a+b)^{3}=a^{3}+b^{3}+3 a b(a+b)$$